Step by step analysis toward optimal MTF algorithm using an edge test device - Donovan, Molly; Zhang, Da; Liu, Hong (Journal of X-ray science and technology, 2009)
Comprehensive research focus on the use of an edge test device for accurate determination of the modulation transfer function (MTF) in x-ray imaging has resulted in the development of numerous edge processing algorithms. While the overall results of the relative algorithms have been compared, the individual steps within the algorithms have not previously been evaluated for similarities and differences that could significantly affect the resultant MTF. Therefore a step by step investigation to evaluate the alternative methods for each step separately holds the potential to provide insight into improving the overall algorithm by optimizing the method employed for each step. Thus this research study focused on comparing methods applicable for each step comprising the edge algorithm and providing a step by step guide for implementing the optimal algorithm based on given experimental conditions. In addition, new methods and combinations of methods were investigated in several of the algorithm steps, and were determined to provide comparable, if not superior, results to the existing methods. This included the use of different numbers of rows and columns in the region of interest (ROI) for determining the edge spread function (ESF), implementing a new three-step ESF filtering approach, and applying a median filter in both the ESF and line spread function (LSF) smoothing steps.